Phylogenetic analysis of mitochondrial genes of Malaysian tupaia reveals composite species in tupaia glis - Jayaraj V.K; Ahmad Sofiman Othman; Shahrul Anuar Mohd Sah; Seri Intan Mokhtar (Universiti Malaysia Kelantan, 2015)
Recent morphometric analysis on T. glis in Peninsular Malaysia indicates that there were more than one morphotypes in this species. Thus this study attempts to examine this phenomenon using mitochondrial DNA sequences of Cyt b and CO1 genes. A total of 74 DNA sequences for both genes were generated using available universal primers. Samples from Southern Thailand were found to be misidentified as T. glis when in fact these samples clustered with T. belangeri while one T. tana from Borneo was miss-identified as T. minor. The phylogenetic trees showed that there are at least one confirmed morphotype of Tupaia (new Tupaia sp.) that have yet to be described. The results also showed that the separation of T. glis morphotype 1 and 11 were visible in the combined genes tree, congruent with the morphometric phylogeny but had poor phylogenetic support.